2021
DOI: 10.31489/2021no4/14-19
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Analysis of Nickel Ferrite Synthesized by Co-Precipitation Method

Abstract: The Nickel ferrite has been synthesized by co-precipitation method. X-ray diffraction pattern confirms the formation of cubic spinel structure with lattice constant 8.347Å. Structural properties like X-ray density, average crystalline size, bond length, dislocation density and microstrain have been studied. The scanning electron microscope images show grain of bead structures. The Fourier transform infrared spectroscopy spectrum of nickel ferrite under investigation reveals the formation of a cubic spinel stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…By understanding the relationship between synthesis methods and structural properties, it is possible to optimize the synthesis process and tailor the properties of ferrites for specific applications [14,15]. Mn(x)Zn(1-.x)Fe204 Co-precipitation and ceramic methods have been used to synthesis ferrites [10,16,17]. The physical and structural, of these samples have been investigated and the final ferrite product has been identified using established analytical and experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…By understanding the relationship between synthesis methods and structural properties, it is possible to optimize the synthesis process and tailor the properties of ferrites for specific applications [14,15]. Mn(x)Zn(1-.x)Fe204 Co-precipitation and ceramic methods have been used to synthesis ferrites [10,16,17]. The physical and structural, of these samples have been investigated and the final ferrite product has been identified using established analytical and experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The condition of stability of nanostructures entirely determines the time and operating conditions, as well as the scope of their application [1][2][3]. In contrast to massive samples for which, in most cases, the mechanisms of degradation are well enough studied, which has allowed for the development of a number of methods to protect materials from the negative impact of external factors, for nanostructures and nanocomposites, all is not so transparent and clear [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, iron-containing nanoparticles modified in various ways have great prospects, which lie in the possibility of increasing the efficiency of their use in hyperthermia. For example, it was shown in [14] that the formation of nanoparticles of the CuFe 2 O 4 type leads to an increase in the specific absorption rate (SAR) by a factor of 1.5-2 compared to Fe 3 O 4 nanoparticles. Similar effects were established in [15], where it was shown that the formation of magnetic Cobalt ferrite nanoparticles with a reverse spinel structure leads to an increase in the efficiency of their use in magnetic hyperthermia.…”
Section: Introductionmentioning
confidence: 99%